1991
DOI: 10.1002/bit.260380508
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm detachment mechanisms in a liquid‐fluidized bed

Abstract: Bed fluidization offers the possibility of gaining the advantages of fixed-film biological processes without the disadvantage of pore clogging. However, the biofilm detachment rate, due to hydrodynamics and particle-to-particle attrition, is very poorly understood for fluidized-bed biofilm processes. In this work, a two-phase fluidized-bed biofilm was operated under a constant surface loading (0.09 mg total organic carbon/cm(2) day) and with a range of bed height (H), fluid velocities (U), and support-particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
2
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(92 citation statements)
references
References 8 publications
5
84
2
1
Order By: Relevance
“…Reynolds number (Chang et al 1991) In this study, since the medium is fixed, there is no attrition effect. Therefore turbulence effect could be the major factor that increases the detachment pressures, and caused the biofilm to become denser and thinner.…”
Section: Glass Beads Concentrations (G/l)mentioning
confidence: 99%
See 1 more Smart Citation
“…Reynolds number (Chang et al 1991) In this study, since the medium is fixed, there is no attrition effect. Therefore turbulence effect could be the major factor that increases the detachment pressures, and caused the biofilm to become denser and thinner.…”
Section: Glass Beads Concentrations (G/l)mentioning
confidence: 99%
“…In a study to evaluate the essential role of hydrodynamic shear force in the formation of biofilm, Liu and Tay (2002) pointed out that biofilm density quasi-linearly increases with the increase of shear stress. Chang et al (1991) discovered that the medium concentration and the turbulence indicated by Reynolds numbers, significantly affected biofilm density and thickness of a fluidized bed biofilm reactor. In this type of reactor, increasing medium concentration can be associated with increasing attrition due to particle-to-particle contacts and increasing turbulence correlates flow fluctuations that could create forces normal to the biofilm, i.e.…”
Section: Significance Of Aob Cells In the Biofilm And Suspended Growtmentioning
confidence: 99%
“…Reactor geometries are designed to expose high surface areas of the biofilm to flow, such as porous media [18,99] or fibres [47,94], and biomass effluent and other quantities measured.…”
Section: Flow Cellsmentioning
confidence: 99%
“…The inter-polymeric bonds that provide the matrix with its mechanical resilience and structural integrity must either be separated from cell surface proteins, enzymatically lysed, or overcome by tensile forces deriving from the external fluid shear [40], before cells can escape the biofilm envelope. Erosion of single cells, multi-cellular clusters (which maintain their resistance to antibiotics [36]) and sudden large-scale sloughing events also result from fluid shear [23], limiting biofilm thickness [18].…”
Section: Mechanically-induced Detachmentmentioning
confidence: 99%
See 1 more Smart Citation